Zakat Institution in Malaysia: Problems and Issues - Ab Rahman, A; Alias, MH; Omar, SMNS (Univ Sultan Azlan Shah, 2024)
Zakat administration in Malaysia is a State matter in particular relating to the passing of regulations and statutes. The respective Heads of States (the rulers) are heads of Islam as enshrined in the Federal Constitution. This paper gives a chronicle of the transformation and phases of development of zakat institution in Malaysia. Zakat institution can play an important role in complementing the Government's poverty eradication effort although its scope is for the poor and needy Muslims only. Besides the poor and needy, there are other beneficiaries allowed by the Syariah. Its success would also help to buffer the effects of recession of the economy on the poor through capacity building and mind-set transformation. The effectiveness of the zakat institution in carrying out its duties would depend on a number of factors viz. expansion of new resources for zakat, the collection of zakat from tangible and intangible properties, systematic zakat management, efficient zakat distribution and the thoroughness of implementation of Islamic rules. The article would discuss on matters that should be dealt with in order to improve zakat institutions in Malaysia in terms of the inefficiency issue, prospective payers, and capacity building.